Fruit Leather Melon Formulation with Supplementation of Pineapple Puree, Carrageenan and Sorbitol - Aini Nur; Nurfadilah Azzahra Salma; Setyawati Retno; Sustriawan Budi; Eko Kusuma Kurniawan Ruly; Sabila Arsyistawa Hadana; Putri Roro Arianti Embun (E3S Web of Conferences)
Melon is a fruit with high water content so that processing is needed to increase its economic value and shelf life. An alternative that can be done is to process it into fruit leather. The characteristics of fruit leather are influenced by pectin, sugar, and acid. The purpose of this study was to determine the optimum formula based on the addition of pineapple puree, carrageenan, and sorbitol to the chemical and sensory characteristics of melon fruit leather. The study used Response Surface Methodology with a Central Composite Design. The factors studied were pineapple puree, carrageenan, and sorbitol. The research stages carried out included preliminary research, formulation optimization, data analysis, verification and validation, and characterization of the optimum product. The results showed that increasing the concentration of pineapple puree caused an increase in water content, total sugar, titrated acid, and a decrease in texture sensory, while preferences tended to be stable. Increasing the carrageenan concentration caused an increase in total sugar and texture, but decrease in water content, titrated acid, and preference. Increasing the sorbitol concentration caused an increase in texture and preference, but a decrease in water content, total sugar and titrated acid. The optimum formula obtained of melon fruit leather based on 15% pineapple puree, 0.6% carrageenan, and 8% sorbitol with a desirability level of 0.723. The optimum formula had a water content of 17.9%; total sugar 20.0%; titratable acid 1.6%, which was lower compared to the control. Vitamin C content 52.2 mg/100 g; soluble solids of 83.2 oBrix, colour of 3.9; taste of 3.6, texture of 3.7; and preference 3.8; which were higher compared to the control. While the aroma sensory 3.044 was the same as the control.